Pengaruh pH Awal dan Suhu selama Penyimpanan terhadap Stabilitas Ekstrak Pewarna Kulit Buah Jeruk Mandarin (Citrus reticulata) - Perdisen, Alfridus Sandro Dacosta; Wartini, Ni Made; Hartiati, Amna (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2021)
The orange peel of Mandarin oranges contains carotenoid compounds which have potential as natural yellow and orange dyes and also as a source of antioxidants. The dye obtained from Mandarin orange peel has unstable properties. The purpose of this study was to know the effect of initial pH and temperature during storage on the stability of the Mandarin orange peel dye extract and determine the best initial pH and temperature during storage to maintain the stability of the Mandarin orange peel dye extract (Citrus reticulata). The experiment of this study used Completely Randomized Design with two factors. The first factor is initial pH consisting of three levels: pH 4, 7, and 10. The second factor is temperature during storage consisting of two levels: 4±3ºC and 28±3ºC. The results showed that initial pH had significant effect (P<0.01) on carotenoids, antioxidant capacity, brightness (L*), redness (a*), and yellowess (b*). The temperature during storage had significant effect on carotenoids, antioxidant capacity, brightness (L*), and yellowess (b*) but had not significant effect (P>0.05) on redness (a*). The dye extract of Mandarin orange peel was more stable at the storage conditions of pH 7 (neutral) and cold temperature (4±3ºC) during 4 weeks storage with decreased of carotenoids, antioxidant capacity, increase in brightness (L*), decrease in redness (a*), and decrease in yellowess (b*) successively was 42,96%; 21,02%; 26,36%; 20,89 dan 16,89%. Keywords: Mandarin orange peel extract, carotenoids, pH, temperature, color stability.